Exposure to chromium during pregnancy and longitudinally assessed fetal growth: Findings from a prospective cohort. (December 2018) - Peng, Yang; Hu, Jie; Li, Yuanyuan; Zhang, Bin; Liu, Wenyu; Li, Han; Zhang, Hongling; Hu, Chen; Chen, Xiaomei; Xia, Wei; Lu, Shi; Xu, Shunqing
Abstract: Background: Prenatal exposure to chromium may be associated with reduced birth weight; however, critical windows of such exposure for fetal growth are unclear. Objective: Our study was aimed to assess trimester-specific associations of chromium exposure with fetal growth parameters measured repeatedly by ultrasound and birth size, and to see whether these associations were modified by fetal sex. Methods: We conducted a prospective cohort of 3041 women in Wuhan, China, from 2013 to 2016. Chromium concentrations were measured in maternal urine samples collected in the 1st, 2nd, and 3rd trimesters using an inductively coupled plasma mass spectrometry. We calculated standard deviation scores for ultrasound measured head circumference, abdominal circumference (AC), femur length, and estimated fetal weight (EFW) at 16, 24, and 31 weeks of gestation. Linear regressions with generalized estimating equations were used to estimate the associations of specific gravity-adjusted urinary chromium concentrations in each trimester with fetal growth parameters and birth weight, birth length, and ponderal index. Results: Inverse associations of chromium exposure in the 1st trimester with fetal growth parameters at 31 weeks of gestation were observed, resulting in significant reductions in AC of −5.4% (95% confidence interval [CI]: −9.6%, −1.2%) and EFW of −5.6% (95% CI: −9.8%, −1.4%) per unit increase in natural logarithm transformed urinary chromium concentration. Urinary chromium concentration in the 2nd trimester was also associated with reductions in AC of −7.0% (95% CI: −12.5%, −1.4%) and in EFW of −5.0% (95% CI: −10.6%, 0.6%) at 31 weeks, and these inverse associations were evident in boys (reduction in AC of −13.9% [95% CI: −21.1%, −6.7%]; EFW of −9.5% [95% CI: −16.9%, −2.0%]) but not in girls (increase in AC of 2.9% [95% CI: −5.7%, 11.5%]; EFW of 1.5% [95% CI: −6.8%, 9.8%]) (both p ineraction  < 0.05). Moreover, one-unit increase in urinary chromium concentrations in the 1st and 2nd trimesters were both associated with significant reductions in ponderal index of −0.11 kg/m 3 (95% CI: −0.19, −0.03 kg/m 3 ) and −0.15 kg/m 3 (95% CI: −0.27, −0.03 kg/m 3 ), respectively. Conclusion: Our findings suggest that chromium may be a toxic metal for fetal growth. Early and mid-pregnancy seem to be the most vulnerable period for fetal exposure to chromium, but these results need further confirmation. Highlights: Trimester-specific associations of chromium with fetal growth were assessed. Higher chromium levels were associated with reduced fetal growth. Early and mid-pregnancy may be critical windows of chromium exposure for fetal growth.